The Position of Ethics in Research Methodology of Educational Sciences after 1989 in the Czech Republic - Dopita, Miroslav; Grecmanova, Helena (Communications - Scientific letters of the University of Zilina, 2018)
Ethics is one of the themes of educational sciences. Its position is in disciplines such as the history of pedagogy, philosophy of education, the theory of education, general pedagogy, didactics, andragogy or adult education, special pedagogy, research methodology of educational sciences, school legislation and other. Ethical norms were influenced by ideology in the Czech and Slovak environment before 1989. Ethics in educational sciences have gradually been revised after 1989. The presented paper focuses on the analysis of scientific texts on research methodology of educational sciences (pedagogy, andragogy or adult education, special pedagogy), dealing with research ethics and published in publishing houses of nation-wide distribution (Grada, Karolinum, Paido, Portal) in 1990-2015. Examined are ethical aspects of both quantitative and qualitative researches with regard to the development of contemporary global as well as local society.